Beban Ganda Perempuan Di Desa Sitapongan Provinsi Sumatera Utara Di Kaji Dari Perspektif Konseling Feminis - Pardede, Refina; Engel, Jacob Daan; Tampake, Tony (Sekolah Tinggi Teologi Kharisma, 2024)
This research is motivated by the presence of the double burden phenomenon which very often create gender injustice for women, especially in Sitapongan Village, North Sumatra Province which experiencing a double burden. Apart from playing a role in the domestic realm such as taking care of household, being a wife and being a mother to their children, they also playing a role in the public sphere that is working as farmer. The double burden that experienced by women in this village is caused by the unequal division of gender roles between men and women in their family. The purpose of this research is to analyze the double burden and impacts that experienced by women with double burdens in Sitapongan Village. In this research, the writer used a qualitative research method and ethnographic approach with data collection techniques through observation, interviews, and documentation. Then, the scalpel in this research is feminist counseling theory because it is can be used as a new change in the world of counseling and can be a tool to see the phenomenon of the double burden experienced by women in Sitapongan Village. Counseling theory with a feminist approach encourages individuals to pay attention to societal patterns of change and encourage social change that emphasizes gender equality as a way to create a change. Furthermore, the purpose of feminist counseling is to increase awareness in the division of gender roles or burdens.Penelitian ini mengangkat fenomena beban ganda yang sering menimbulkan ketidakadilan gender terhadap perempuan di Desa Sitapongan, Sumatera Utara. Perempuan di desa ini tidak hanya menjalankan peran domestik seperti mengurus rumah tangga, menjadi istri, dan ibu, tetapi juga bekerja di ranah publik sebagai petani. Beban ganda ini terjadi akibat pembagian peran gender yang tidak seimbang dalam keluarga. Penelitian ini bertujuan menganalisis jenis beban ganda yang dialami perempuan serta dampaknya. Dengan menggunakan metode kualitatif pendekatan etnografi melalui observasi, wawancara, dan dokumentasi, penelitian ini menggunakan teori konseling feminis sebagai kerangka analisis. Teori ini menekankan pentingnya perubahan sosial yang mendorong kesetaraan gender. Konseling feminis berupaya meningkatkan kesadaran akan pembagian peran gender yang adil, sekaligus menawarkan perspektif baru dalam memahami dan mengatasi beban ganda perempuan.